2014
DOI: 10.1016/j.bbr.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Classifying social anxiety disorder using multivoxel pattern analyses of brain function and structure

Abstract: HighlightsSocial anxiety disorder (SAD) is a common and disabling psychiatric disorder.Support vector machines (SVM) were trained to separate SAD from controls.Neural face processing in the fear network separated SAD patients from controls.Gray matter volume alterations over the whole brain separated SAD from controls.SVM classifiers may be useful for identifying imaging biomarkers of SAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 25 publications
(30 reference statements)
6
56
0
Order By: Relevance
“…However, subsequent studies could not substantiate these results to the same degree Shenas et al, 2014). Two studies on SAD have been published in small samples, reporting accuracies above 80% (Frick et al, 2014;Liu et al, 2013). Multivariate patterns in these studies were derived from different MRI modalities indicating that features relevant for disorder classification can be extracted and analysed across modalities.…”
Section: Obsessive Compulsive Social Anxiety Post-traumatic Stress mentioning
confidence: 94%
See 1 more Smart Citation
“…However, subsequent studies could not substantiate these results to the same degree Shenas et al, 2014). Two studies on SAD have been published in small samples, reporting accuracies above 80% (Frick et al, 2014;Liu et al, 2013). Multivariate patterns in these studies were derived from different MRI modalities indicating that features relevant for disorder classification can be extracted and analysed across modalities.…”
Section: Obsessive Compulsive Social Anxiety Post-traumatic Stress mentioning
confidence: 94%
“…Multivariate patterns in these studies were derived from different MRI modalities indicating that features relevant for disorder classification can be extracted and analysed across modalities. In general informative features were found to be distributed across widespread brain areas (Frick et al, 2014;Liu et al, 2013) and not easily localisable to brain regions usually associated with anxieties, such as the limbic lobes (Damsa et al, 2009). An additional study showed that structural images can be used as a diagnostic medium for different specific phobias, which could reliably be classified based on grey and white matter densities (Lueken et al, 2014).…”
Section: Obsessive Compulsive Social Anxiety Post-traumatic Stress mentioning
confidence: 98%
“…With respect to correlations between anxiety and brain structures, controversies remain. One study suggested that social anxiety disorder implicates GM alterations over the whole brain 24 . On the other hand, this syndrome may be characterized by disrupted neural activity in the fear network composed of the amygdala, anterior cingulate cortex, hippocampus, and insula.…”
Section: Discussionmentioning
confidence: 99%
“…The amygdala thus undoubtedly plays a critical role in salience, vigilance‐avoidance and stress processing, and amygdala activity constitutes a potential biomarker for social anxiety, e.g., Ref . However, future research also needs to address some the concerns raised above (and other ones, see Ref ) regarding the role of the amygdala and the emotion network in social anxiety.…”
Section: The Emotion Networkmentioning
confidence: 99%